1996
DOI: 10.1074/jbc.271.20.11979
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Structural Context of a Functional β-Hairpin

Abstract: An approach to obtain new active proteins is the incorporation of all or a part of a well defined active site onto a natural structure acting as a structural scaffold. According to this strategy we tentatively engineered a new curaremimetic molecule by transferring the functional central loop of a snake toxin, sequence 26 -37, sandwiched between two hairpins, onto the structurally similar ␤-hairpin of the scorpion toxin charybdotoxin, stabilized by a short helix. The resulting chimeric molecule, only 31 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 74 publications
0
39
0
2
Order By: Relevance
“…and fasciculins clearly reflect their difference of biological activities. It has been recently shown that a more limited transfer of 7 of the 11 residues forming the curaremimetic site of toxin ␣ within a similar ␤-sheet of charybdotoxin failed to generate a potent curaremitic agonist, mostly for conformational reasons (54). Therefore, to respect the structural integrity of the functional regions, we transferred 42.6% of specific residues (26 of 61 amino acid residues) from fasciculins into toxin ␣ mostly spread over two homogenous areas, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…and fasciculins clearly reflect their difference of biological activities. It has been recently shown that a more limited transfer of 7 of the 11 residues forming the curaremimetic site of toxin ␣ within a similar ␤-sheet of charybdotoxin failed to generate a potent curaremitic agonist, mostly for conformational reasons (54). Therefore, to respect the structural integrity of the functional regions, we transferred 42.6% of specific residues (26 of 61 amino acid residues) from fasciculins into toxin ␣ mostly spread over two homogenous areas, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, immunogens designed by epitope transplantation have elicited structurespecific responses targeting a snake toxin, the yeast transcription factor GCN4, the severe acute respiratory syndrome coronavirus S glycoprotein, and the human immunodeficiency virus 2F5 and 4E10 epitopes [171][172][173][174]. However, the ability to graft a motif onto a scaffold is still limited by the complexity of the motif and the availability of scaffolds with suitable structures.…”
Section: Epitope Graftingmentioning
confidence: 99%
“…b) The synthesis of short oligopeptides (less than 40 residues) termed as mini-proteins [5][6][7][8][9] that reproduce, in part, the function of much larger proteins, by transferring the active sites to small and stable natural scaffolds.…”
Section: Introductionmentioning
confidence: 99%